Illegal trade of crocodylians in Colombia: Spatiotemporal dynamics and implications on conservation efforts - Edison D. Bonilla‐Liberato; Maria C. Ojeda‐Rojas; Venetia Briggs‐Gonzalez; Frank J. Mazzotti; Sergio A. Balaguera‐Reina (Conservation Science and Practice, 2025)
Abstract Crocodylian conservation efforts have encountered significant obstacles from species overhunting to negative local perception. While conservation strategies such as sustainable use have helped the recovery of several crocodylian species around the world, its effectiveness has been limited by illegal wildlife trade as well as changes in control and trade policies. We assessed the spatiotemporal dynamics of illegal crocodylian trade in Colombia from 2010 to 2022 based on data collected by regional and district environmental authorities and discussed its implications on conservation efforts. Illegal trade of crocodylians in Colombia has been predominantly characterized by spectacled caimans (Caiman crocodilus, 97.37%). However, most of the species inhabiting the country (especially American crocodiles—Crocodylus acutus and black caiman—Melanosuchus niger) have been seized/confiscated at least once by law enforcement in the last decade, with the exception of Orinoco crocodiles (Crocodylus intermedius). Illegal trade was most prominent in departments from the Caribbean region especially those with spectacled caiman farms. A generalized additive model (deviance explained 55.9%, effect estimate = 7.35 ± 0.18, n = 13) showed very strong evidence of an effect of CITES exports (leather products and in a lesser extend tails) on the number of spectacled caimans illegally traded in Colombia, meaning spectacled caiman leather products and tails were able to predict illegally traded spectacled caiman in the country. Overall, local demand, cultural practices, and low economic conditions appear to exacerbate illegal trade of crocodylian in Colombia.